The EU Sanctions Policy: A Thorny Path of Transformation - L. D. Oganisyan (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
In recent years, the rising international tensions have raised for the EU leadership pressing questions on the prospects for both the internal development of the union and its global positioning. Against this backdrop, the analysis of the EU sanctions policy as a key tool of its foreign policy strategy is of particular interest. Such an analysis can not only help identify the specific features of the European Union as a subject of restrictions, but also reach a better understanding of the current evolutionary trends of this integration association on the whole. The first section examines the key institutions responsible for the development of the EU sanctions policy, as well as the principles and mechanisms underlying the adoption and implementation of the relevant measures. The author emphasizes the targeted and value-based character of the EU sanctions policy, its commitment to multilateralism and concerns about possible adverse humanitarian effects. The second section traces the evolution of the EU sanctions policy over the period from 1992 to 2022. It shows that it was as early as the 2010s that the EU countries started to switch from using sanctions primarily as a means of conveying an addressee a certain ‘political message’ designed to ensure human rights and democratic values, to harnessing them as an economic leverage. At the same time, evident disagreements emerged between the EU and the United States on secondary sanctions. All this led the EU leadership to realize the need to strengthen its sanctions policy, as well as its strategic autonomy in general. The third section analyzes the key aspects of the qualitative transformation of the EU sanctions policy that began in 2022. The author notes that along with a sharp increase in the number of sanctions against Russia provoked by the beginning of the special military operation in Ukraine, the most important element of this transformation was the intensification of the EU’s efforts to combat sanctions evasion. All this indicates the growing readiness of the EU, which previously condemned the practice of extraterritorial sanctions, to apply sanctions measures beyond its borders. At the same time, the European Commission plays an increasingly active role in the development of restrictive measures. This may significantly change the institutional balance within the EU in its favor, contributing to strengthening the supranational principle. The prospects for the implementation of these tendencies, however, will largely depend on the international context and the ability of the EU leadership to reconcile competing interests of the member states.